Supervisory Board Structure and Group Dynamics as Determinants of Company Performance - Marchewka, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The role of supervisory boards (SB) in shaping company performance is one of the key issues of corporate governance. The article describes a study comparing the importance of the structure and functioning of SB for company performance. The study examined 291 companies listed on the Warsaw Stock Exchange (from 2010 to 2013). The data on the structure of SB was based on the study of board member CVs, while in the analysis of group dynamics data from the survey was used. The analysis showed that the diversity of educational degrees and the size of the board are important features of the structure, but the direct relationship between the structure and company performance is weak. It was confirmed that the effectiveness of SB depends on group processes, such as cohesion, cognitive conflict and effort norms, which are affected by the structure of education. The results provide insight into the issue and enable the development of group processes conducive to board effectiveness and company performance.